Teachers' Impressions on the Use of Digital Media in Early English Learning for Early Childhood Students - Zainuddin; White , Jayne (Universitas Islam Zainul Hasan Genggong, 2023)
English has received a lot of attention recently and is often used as a centerpiece program in early childhood education. Successful learning requires innovation in media adapted to the age and characteristics of early childhood. This research aims to determine teachers' impressions of the use of digital learning media in early English teaching for preschool-aged children. This type of research is descriptive quantitative with a research sample of early childhood teachers in Probolinggo city totaling 36 people determined using a total sampling technique. The results of the research explain that teachers' impressions of the use of digital learning media in early English teaching for early childhood are in a good category. In other words, even though teachers' ability to use digital devices for learning activities is still quite low, teachers view this digital media as having the potential to increase children's interest and motivation in learning, apart from that it is also useful in stimulating the knowledge and skills of preschool-aged children. Therefore, based on the results of this research, follow-up is also needed in the form of digital literacy training for early childhood teachers in Probolinggo city in learning preschool-aged children, especially early English.